Coking plant wastewater treatment in integrated systems combining volume coagulation and advanced oxidation with pressure membrane techniques = Oczyszczanie poprocesowych wód koksowniczych w układach zintegrowanych łączących metody koagulacji objętościowej i pogłębionego utleniania z ciśnieniowymi technikami membranowymi - Mielczarek, Karolina; Bohdziewicz, Jolanta; Kwarciak-Kozłowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article compares the efficiencies of coke plant wastewater treatment in the integrated systems that combine physicochemical and chemical purification methods with ultrafiltration and reverse osmosis. The wastewater treated came from the "Coke Plant Czestochowa New".
Keywords: ścieki koksownicze; koagulacja objętościowa; odczynnik Fentona; ciśnieniowe techniki membranowe; ultrafiltracja; coke plant wastewater; volumetric coagulation; Fenton's reagent; pressure membrane techniques; ultrafiltration